ANALYSIS FARMING CHILLI RED ( CAPSICUM ANNUM L. ) VARIETY HOT BEAUTY (STUDIES CASE IN SEI MENCIRIM VILLAGE, KUTALIMBARU DISTRICT, DELI SERDANG REGENCY ) - Siska Yulianita; Dian Dhika; Irshad Ahmad Reshi (CV. Radja Publika, 2024)
The purpose of this study was to determine: 1) The average cost and revenue of red chili farming per hectare in one planting season in Sei Mencirim Village, Kutalimbaru District, Deli Serdang Regency. 2) The average income of red chili farming per hectare in one planting season in Sei Mencirim Village, Kutalimbaru District, Deli Serdang Regency. 3) The average R/C of red chili farming in one planting season in Sei Mencirim Village, Kutalimbaru District, Deli Serdang Regency. The type of research used in this study is a case study, which is an in-depth study of a particular characteristic of the research object, this research is in Sei Mencirim Village, Kutalimbaru District, Deli Serdang Regency. The sampling technique was carried out by census of 30 farmers. The results of the study indicate that: 1) The total cost was Rp. 34,385,907.09, the revenue was Rp. 57,600,000 per planting season, obtained from an average red chili harvest of 6,400 kilograms at a price of Rp. 9,000 per kilogram. 2) The income is Rp. 73,940,928.57 per hectare per planting season. 3) The R/C (Revenue Cost Ratio) is Rp. 2.51, meaning that red chili farmers have earned a profit of Rp. 2.51.